2021
DOI: 10.1115/1.4051623
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method to Enhance Oil Recovery by Inter-Fracture Injection and Production Through the Same Multi-Fractured Horizontal Well

Abstract: Conventional enhanced oil recovery (EOR) approaches are inefficient in the unconventional reservoirs. This paper provides a novel approach to enhance oil recovery from unconventional oil reservoirs through synchronous inter-fracture injection and production (SiFIP) and asynchronous inter-fracture injection and production (AiFIP). The compartmental embedded discrete fracture model (cEDFM) is introduced to simulate complex fracture geometries to quantitatively evaluate the performance of SiFIP and AiFIP. EOR per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…CO 2 foam can expand the application range of the viscosity reducer and push the viscosity reducer into a deeper position of the reservoir . On the other hand, injection of CO 2 can effectively reduce greenhouse gas, , which is conducive to CCUS (carbon capture, utilization, and storage). Therefore, CO 2 foam is more capable of pushing the foam to enter a deeper reservoir than N 2 foam in the heterogeneous reservoir . Like the application of N 2 foam in the heavy reservoir, the surfactant solution , also has be added into the CO 2 foam to improve the foam performance, and nonionic surfactants , are used to enhance the foam stabilization in the high-temperature and extremely high-salinity heavy oil reservoir. , In addition, Li et al improved the thermal stability of CO 2 foam under reservoir conditions; four different types of surfactants were evaluated by high-temperature- and high-pressure-foaming devices .…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 foam can expand the application range of the viscosity reducer and push the viscosity reducer into a deeper position of the reservoir . On the other hand, injection of CO 2 can effectively reduce greenhouse gas, , which is conducive to CCUS (carbon capture, utilization, and storage). Therefore, CO 2 foam is more capable of pushing the foam to enter a deeper reservoir than N 2 foam in the heterogeneous reservoir . Like the application of N 2 foam in the heavy reservoir, the surfactant solution , also has be added into the CO 2 foam to improve the foam performance, and nonionic surfactants , are used to enhance the foam stabilization in the high-temperature and extremely high-salinity heavy oil reservoir. , In addition, Li et al improved the thermal stability of CO 2 foam under reservoir conditions; four different types of surfactants were evaluated by high-temperature- and high-pressure-foaming devices .…”
Section: Introductionmentioning
confidence: 99%
“…Meszaros et al found that up to 70% of the oil reservoirs produced by gravity-stabilized gas flooding was by N 2 injection . The study found that gas-assisted gravity drainage (GAGD) technology can improve sweep efficiency and oil displacement efficiency and can effectively improve oil recovery compared with conventional gas flooding. The results showed that GAGD technology could improve the recovery rate by 100% in laboratory experimental tests and 87–95% in field application…”
Section: Introductionmentioning
confidence: 99%
“…Gas reservoirs whose formation temperature and pressure exceed the critical point of CO 2 are the most suitable sites for CO 2 storage. Therefore, from the perspective of economic benefits, it is a hot research topic to achieve enhanced natural gas recovery by injecting CO 2 into gas reservoirs and using its own conditions for storage [12]. There are two schemes to reduce the concentration of carbon dioxide in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%